The role of key actors in the promotion of local community development the case of KALAHI-CIDSS projects in Janiuay, Iloilo. - Bartolome, Carie Fel M. (2008.)
This research is centred on the research problem-what are the roles of the key actors in the promotion of local community development in the case of the Kapit-bisig Laban sa Kahirapan-Comprehensive and Integrated Delivery of Social Services (Kalahi-CDISS0 projects in the municipality of Janiuay, Iloilo. Firstly, there is need to explain local community devleopment in the Kalahi-CDISS projects in Janiuay, Iloilo. Next, the paper proceeds to described the resources that are being employed in Kalahi-CDISS in Janiuay in order to meet its goals. Then, the paper directs on the description of the roles of the key actors in the Kalahi-CIDSS projects in Janiuay, Iloilo. The last objective of this paper is to described the developmental outcomes brought by the projects to the people of Janiuay.
Thesis (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Local community development -- KALAHI-CIDSS projects